Rapid Thermal Shutdown of Deep‐Eutectic‐Polymer Electrolyte Enabling Overheating Self‐Protection of Lithium Metal Batteries - Zengqi Zhang; Gang Li; Xiaofan Du; Lang Huang; Guohong Kang; Jianjun Zhang; Zili Cui; Tao Liu; Ling Ni; Yongcheng Jin; Guanglei Cui (Advanced Science)
Abstract Safety concerns and uncontrollable dendrite growths have severely impeded the advancement of lithium‐metal batteries. Herein, a safe deep‐eutectic‐polymer electrolyte with built‐in thermal shutdown capability is proposed by utilizing hydrophobic association of methylcellulose within a novel deep‐eutectic‐solvent. Specifically, at elevated temperatures, methylcellulose chains aggregate to form dense polymer networks due to hydrophobic association and break the solvation structure equilibrium inside the deep‐eutectic system through encapsulating Li+ in polymer matrix, leading to quick solidification of the electrolyte. The solidified electrolyte obstructs Li+ transports and terminates electrochemical processes, protecting LMBs from unstoppable exothermic chain reactions. The accelerating rate calorimeter tests of 1 Ah pouch cells demonstrate that the as‐prepared electrolyte significantly improves the onset self‐heating temperature from 73 °C for conventional electrolytes to 172 °C and prolongs the thermal runaway waiting time more than 20 hours. More impressively, benefiting from its favorable electrochemical performance, this polymer electrolyte enables LiNi0.8Mn0.1Co0.1O2||Li batteries to retain 92% capacity over 200 cycles and LiFePO4||Li batteries to maintain 90% capacity after 500 cycles. This research paves a promising avenue for enhancing both the safety and electrochemical performance of high‐energy‐density LMBs.